2017
DOI: 10.1111/vox.12534
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of haemostatic function of PAS‐C–platelets vs. plasma–platelets in reconstituted whole blood using impedance aggregometry and thromboelastography

Abstract: Our findings demonstrate that the function - aggregation and CD62P responsiveness - of PAS-C-platelets in reconstituted whole blood is inferior to that of plasma-platelets, which may have implications in the setting of massive transfusions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 29 publications
2
6
0
Order By: Relevance
“…The observation that most articles reporting CSPs suspended in plasma alone showed higher hemostatic activity than RTP controls whereas CSPs stored in plasma plus PAS were usually no different than RTP controls is similar to that reported by Van Hout et al 53 in vitro. In this article, whole blood was reconstituted using components: RBCs, plasma, and either RTPs in plasma alone or RTPs suspended in plasma and PAS (30:70).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The observation that most articles reporting CSPs suspended in plasma alone showed higher hemostatic activity than RTP controls whereas CSPs stored in plasma plus PAS were usually no different than RTP controls is similar to that reported by Van Hout et al 53 in vitro. In this article, whole blood was reconstituted using components: RBCs, plasma, and either RTPs in plasma alone or RTPs suspended in plasma and PAS (30:70).…”
Section: Discussionsupporting
confidence: 82%
“…47 Conversely, the addition of PAS to plasma not only may result in reduced hemostatic function of CSPs but also increases the crystalloid volume transfused during the resuscitation, potentially resulting in inferior clinical outcomes. 53 The observation of no consistent trend between time to cold storage and CSP hemostatic activity versus RTPs is consistent with the outcome of a recent study that was published after the searches for this review were performed. This study reported that refrigeration of platelets after 4 days' storage at room temperature can restore hemostatic function to a comparable level as CSP cooled the day after collection.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Storage lesions of PLT concentrates were assessed [13-15,21,55-,57] during 7-13 days of storage ( Table 2). In most cases, tests were performed by dilution with a plasma T, R Pooled, plasma, 22 or 30°C, 8 days Table 2 Johansson 2008 [55] T Pooled, PAS-B, RT, 7 days Table 2 Middelburg 2013 [56] T Pooled, plasma, riboflavin, RT, 7 days Riboflavin: MA↓ Table 2 Van Hout 2017 [57] T Pooled, plasma/ PAS-C, RT, 13 days pool to a fixed PLT concentration. Experiments showed, in general, increasing clotting rates and clot strength when PLT concentration was raised and the opposite when samples were diluted.…”
Section: Platelet Concentrates: Storage Lesion Of Fresh Plateletsmentioning
confidence: 99%
“…While the above example is purely mathematical and needs further clinical confirmation, in vitro studies showed that the dilution effect of platelets in PAS may be true, or at least warrants further investigation. Van Hout et al [32] reconstituted whole blood and used either platelets stored in plasma or in PAS-C. Their in vitro study showed that platelet aggregation responses as measured with the Multiplate aggregation assay with ADP and TRAP as stimulus declined during 7 days of storage and were always lower in PASstored platelets; collagen and ristocetin responses also declined over time, but no difference was seen between plasma-or PASstored platelets. Thromboelastographic parameters (measured with the TEG device), showing the overall ability of this reconstituted whole blood to clot, were not affected.…”
Section: Clinical Outcomes In Surgical Patientsmentioning
confidence: 99%